Global Financial Crisis and Economic Growth: Analysis of The East Asia Economy - Hafeez Hoorani (GoAcademica Research & Publishing, 2020)
In line with the increasingly integrated economy in the midst of globalization, the financial crisis that occurred in one country can easily spread to other countries and become a global financial disaster in a short period of time. In such an event, strong economic fundamentals are essential to defend a country from the effects of a